Viral hepatitis C treatment shortening – what is the limit? - Zarębska-Michaluk, Dorota (Clinical and Experimental Hepatology, 2019)
Successful antiviral treatment for hepatitis C virus (HCV) infection is crucial to prevent progression of the disease and its most serious complications. Therapy options have changed over the years with improvement of treatment efficacy, safety and simplification. They evolved from interferon and ribavirin combination administered for 24-72 weeks through interferon (IFN)-based triple therapies with 24-48 weeks duration to the all-oral, well-tolerated direct-acting antiviral regimens lasting for 8-16 weeks and with almost 100% cure rates. The benefits of shorter treatment duration are cost reduction, access to therapy for more patients, and lower risk of adverse events and nonadherence. This review summarizes data on treatment options, focusing on the recommended durations of different regimens depending on HCV genotype, severity of liver disease and history of previous therapy. According to currently available data, shortening treatment below 8 weeks does not provide additional benefits, although the further simplification of therapy is still a subject of study.